A negative body image contextualization of the self-compassion scale. (September 2022) - Ullrich-French, Sarah; Cox, Anne E.
Abstract: Self-compassion, a style of responding to oneself in times of suffering, is typically measured as a general tendency for how one normally responds using the Self-Compassion Scale (SCS; Neff, 2003). A contextualized adaptation to the SCS could provide a new understanding of how one responds to suffering by providing a standard frame of reference, is more likely to be more predictive of context outcomes, and reduces intraindividual variance (Baird & Lucas, 2011). How a contextualized assessment of self-compassion compares to the original assessment using parallel measures is unknown. The purpose of this study was to explore the use of a modified SCS adapted for the context of responding to the experience of negative body image (BI-SCS). There were 468 participants who completed the SCS and then wrote about a specific negative body image experience (to prime a negative body image experience) before they completed a modified SCS and related constructs. Confirmatory Factor Analysis supported a bi-factor structure consistent with SCS. Correlations with body image outcomes were stronger for the majority of BI-SCS scores compared to the SCS. Unique explained variance of the BI-SCS supported incremental validity. Results show promising initial evidence supporting the use of the BI-SCS for body-related outcomes. Highlights: Assessment of self-compassionate responding to negative body image. Evidence for a contextualized Self-Compassion assessment. Context measure had stronger associations with body image than the trait measure. Unique explained variance using the context specific measure. Parallel measures allowed comparison of all six-dimensions of self-compassion.